A Highly Stable, Capacity Dense Carboxylate Viologen Anolyte towards Long‐Duration Energy Storage. (12th January 2023) - Wu, Wenda; Wang, Abigail P.; Luo, Jian; Liu, T. Leo
Abstract: Aqueous organic redox flow batteries (AORFBs) have received increasing attention as an emergent battery technology for grid‐scale renewable energy storage. However, physicochemical properties of redox‐active organic electrolytes remain fine refinement to maximize their performance in RFBs. Herein, we report a carboxylate functionalized viologen derivative, N, N′‐dibutyrate‐4, 4′‐bipyridinium, (CBu)2 V, as a highly stable, high capacity anolyte material under near pH neutral conditions. (CBu)2 V can achieve solubility of 2.1 M and display a reversible, kinetically fast reduction at −0.43 V vs NHE at pH 9. DFT studies revealed that the high solubility of (CBu)2 V is attributed to its high molecular polarity while its negative reduction potential is benefitted from electron‐donating carboxylate groups. A 0.89 V (CBu)2 V /(NH)4 Fe(CN)6 AORFB demonstrated exceptional energy storage performance, specifically, 100 % capacity retention with a discharge energy density of 9.5 Wh L −1 for 1000 cycles, power densities of up to 85 mW cm −2, and an energy efficiency of 70 % at 60 mA cm −2 . (CBu)2 V not only represents the most capacity dense viologen with pendant ionic groups and also exhibits the longest (1200 hours or 50 days) and the most stable flow battery performance to date. Abstract : A carboxylate functionalized viologen is developed as a capacity dense, highly stable anolyte for aqueous organic redox flow batteries up to 50 days of stable cycling.